The Antecedents Affecting the Job Performance of Private Enterprises - Xiang Li; Teetut Tresirichod (Bright Publisher, 2024)
This study explores the antecedents that affect employee job performance (JP) in private enterprises: organizational culture (OC), work-life balance (WLB), and job satisfaction (JS), and reveals the relationship between these variables.The study used quantitative analysis methods and partial least squares structural equation (PLS-SEM) method to conduct descriptive statistics and analysis on questionnaire survey data of 553 private enterprises above designated size in the food industry in Sichuan Province, China, verifying the theoretical framework and hypothesis relationship.The research results found a significant positive correlation between organizational culture and job satisfaction . Job satisfaction positively affects job performance and plays a mediating role between organizational culture and job performance.In addition, Work-Life Balance significantly increased the strength of the relationship between Organizational Culture and Job Satisfaction. These findings not only enrich the application of social exchange theory and resource security theory in theory, but also provide valuable insights for enterprises to formulate human resource policies and management practices, emphasizing the importance of shaping a positive organizational culture and supporting work- life balance in improving employee job performance. However, this study was only conducted in the food industry of private enterprises in Sichuan Province, and an online questionnaire survey was used, which may affect the universality of the research results and the bias of measurement data. Future research should consider a wider range of regions and industries, and adopt longitudinal designs to explore more variables in order to obtain a more comprehensive understanding.